Editorial - Jegels, Llewellin RG (WritingThreeSixty: Journal or Research and Creative Text, 2021)
2019 is fast coming to an end. It has been a year with highs and lows. In September, the nation wept at the tragic deaths of Jesse Hess, Uyinene Mrwetyana, Leighandre Jegels and other women who became victims of GBV, forcing the country into a state of emergency. This sombre mood was tempered somewhat by a Rugby World Cup victory that allowed the nation to celebrate, albeit briefly, a sense of unity among its diverse people. However, the work of nation-building rests with all of us and, as academics in the Humanities, we seek to ask and research important questions that may lead us to greater insights into our world. This edition of the journal showcases the work of a poet, a visual (photographic) artist and an academic essayist dealing with multiple themes from children’s literature to photography as an agency of change to existentialist questions posed by our poet. We hope, as always, that the reader will find something that gives pause for reflection as we head into the festive season. Best Wishes, Editor-in-chief Llewellin RG Jegels